Revision of Australian species of the dung beetle genus Lepanus (Coleoptera: Scarabaeidae: Scarabaeinae): key to species groups and description of 14 new species from the L. pygmaeus species group - Gunter, Nicole L.; Weir, Thomas A. (Zootaxa, 2019)
Lepanus Balthasar, 1966 (Coleoptera: Scarabaeidae: Scarabaeinae) is one of the most diverse genera of dung beetles in Australasia and includes large numbers of undescribed species. This publication is the first part in an ongoing revision of the Australian members of this genus and outlines ten informal species groups. Fourteen new species that are similar to Lepanus pygmaeus (Macleay, 1888) are described here: Lepanus mckenziei new species from the Pilbara region of Western Australia; Lepanus sauroni new species from coastal regions of the Northern Territory and the Kimberley region of Western Australia; Lepanus gubara new species, Lepanus pecki new species, Lepanus podocarp new species and Lepanus pungalina new species from the Top End, Northern Territory; Lepanus lentil new species from the Top End, Northern Territory and central Queensland; Lepanus crenidens new species, Lepanus lingziae new species, and Lepanus menendezae new species from northern Queensland; Lepanus andersonorum new species, and Lepanus tozerensis new species from Cape York Peninsula, far north Queensland; Lepanus feehani new species from the Australian Wet Tropics; and Lepanus guthrieae new species from the east to west coast of northern Australia. Lepanus pygmaeus is redescribed and a lectotype designated for it. A lectotype is designated for Panelus arthuri Blackburn, 1900. The synonymy of L. pygmaeus with P. arthuri is confirmed. A key to species groups within Lepanus is provided, as well as a key to species in the L. pygmaeus species group.